1984
DOI: 10.1210/endo-114-6-1975
|View full text |Cite
|
Sign up to set email alerts
|

Site of Action of Androgens on Follicle-Stimulating Hormone-Induced Aromatase Activity in Cultured Rat Granulosa Cells*

Abstract: This paper describes experiments on cultured granulosa cells isolated from ovaries of immature rats designed to locate the site of action of androgens on FSH-induced aromatase activity. Treatment of cells during a 36-h induction period with (Bu)2cAMP, 8- BrcAMP , FSH, prostaglandin E2, or cholera toxin resulted in induction of aromatase activity measured as 17 beta-estradiol accumulation during a 6-h test period with testosterone (5 X 10(-7) M) added to medium as substrate. Presence of testosterone (5 X 10(-7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 27 publications
1
15
0
1
Order By: Relevance
“…Previous studies have shown that androgens enhance granulosa cells expression of FSHR in vitro resulting in an increased aromatase expression and an augmented conversion of androgen to estrogen (rat: De Zwart, 1981, 1982;Daniel and Armstrong, 1984;primate: Harlow et al, 1986). However, in rhesus monkeys treated with large doses of exogenous androgens, testosterone was without effect on granulosa cell expression of aromatase and circulating levels of estradiol became reduced (Weil et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that androgens enhance granulosa cells expression of FSHR in vitro resulting in an increased aromatase expression and an augmented conversion of androgen to estrogen (rat: De Zwart, 1981, 1982;Daniel and Armstrong, 1984;primate: Harlow et al, 1986). However, in rhesus monkeys treated with large doses of exogenous androgens, testosterone was without effect on granulosa cell expression of aromatase and circulating levels of estradiol became reduced (Weil et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The production of 19-norandrostenedione in porcine and equine follicular fluid suggests that this compound is involved in the regulation of follicular function [15]. 19-Norandrostenedione, like testosterone, can act in synergy with dibutyryl cAMP to inhibit the germinal vesicle breakdown in porcine oocytes [18]. Similar to androgens, 19-norandrogens can regulate the activity of the 3b-hydroxysteroid dehydrogenase (HSD)/isomerase and affect progesterone synthesis by granulosa cells [19].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas ER-mediated E2 actions are believed to enhance the amount and effectiveness of FSH-stimulated intracellular cAMP without obvious changes in FSH-receptor levels, evidence suggests that androgens may act at a site prior to adenylyl cyclase. For example, neither T nor DHT synergize with (Bu) 2 -cAMP to induce aromatase activity in rat granulosa cells 719 whereas E2 does. 442,720 Instead, ARmediated androgen actions may largely act by increasing the level of FSH receptor in granulosa cells of preantral follicles.…”
Section: Granulosa Cell Differentiationmentioning
confidence: 94%